Genetic diversity assessment of the indigenous goat population of Benin using microsatellite markers - Whannou, Habib Rainier Vihotogbe; Spanoghe, Martin; Dayo, Guiguigbaza-Kossigan; Demblon, Dominique; Lanterbecq, Deborah; Dossa, Luc Hippolyte (Frontiers in Genetics, 2023)
This study assessed the genetic diversity and structure of the indigenous goat population of Benin. Nine hundred Fifty-Nine and fifty-four goats were sampled across the three vegetation zones of Benin (i.e., Guineo-Congolese zone (GCZ), Guineo-Sudanian zone (GSZ), and Sudanian zone (SZ)) and genotyped with 12 multiplexed microsatellite markers. The genetic diversity and structure of the indigenous goat population of Benin were examined using the usual genetic indices (number of alleles Na, expected and observed heterozygosities He and Ho, Fixation index FST, coefficient of genetic differentiation GST), and three different methods of structure assessment (Bayesian admixture model in STRUCTURE, self-organizing map (SOM), and discriminant analysis of principal components (DAPC)). The mean values of Na (11.25), He (0.69), Ho (0.66), FST (0.0350.012), and GST (0.012) estimated in the indigenous Beninese goat population highlighted great genetic diversity. STRUCTURE and SOM results showed the existence of two distinct goat groups (Djallonké and Sahelian) with high crossbreeding effects. Furthermore, DAPC distinguished four clusters within the goat population descending from the two ancestry groups. Clusters 1 and 3 (most individuals from GCZ) respectively showed a mean Djallonké ancestry proportion of 73.79% and 71.18%, whereas cluster 4 (mainly of goats from SZ and some goats of GSZ) showed a mean Sahelian ancestry proportion of 78.65%. Cluster 2, which grouped almost all animals from the three zones, was also of Sahelian ancestry but with a high level of interbreeding, as shown by the mean membership proportion of only 62.73%. It is therefore urgent to develop community management programs and selection schemes for the main goat types to ensure the sustainability of the goat population in Benin.